(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
In contemporary constitutional democracies, the idea of human dignity has emerged as one of the foundational principles of human rights protection and individual freedom. The concept is based on the belief that every individual possesses inherent value and therefore deserves equal respect, liberty, justice, and protection under law. In India, although the Constitution does not expressly define the term “human dignity,” the Supreme Court has progressively interpreted Article 21-guaranteeing the right to life and personal liberty-as encompassing the right to live with dignity. Over the years, the judiciary has interpreted Article 21 in an expansive manner and connected it with several essential rights such as privacy, livelihood, healthcare, shelter, education, reputation, and protection against inhuman treatment. This research paper critically examines the concept of human dignity as a fundamental right with special reference to Article 21 of the Constitution of India. It further undertakes a comparative study of Indian constitutional jurisprudence with major international human rights instruments and foreign legal systems, including the Universal Declaration of Human Rights, the International Covenant on Civil and Political Rights, the International Covenant on Economic, Social and Cultural Rights, the European Convention on Human Rights, South African constitutional law, and German constitutional jurisprudence. The paper analyses how courts across jurisdictions have relied upon dignity as a guiding constitutional value while balancing competing interests of state power, social order, and individual autonomy. The paper suggests that the idea of human dignity has gradually become an important constitutional principle for strengthening the protection of individual rights in democratic societies. However, its abstract nature also creates interpretative challenges, inconsistency in application, and judicial subjectivity. In the Indian context, despite progressive judgments, structural inequalities, custodial violence, poverty, gender injustice, caste discrimination, and digital surveillance continue to threaten the practical realization of dignity. The study concludes that constitutional recognition of dignity must be supported by effective governance, social awareness, and institutional accountability to ensure its meaningful realization.. The constitutional guarantee of dignity can become meaningful only when it is reflected in the everyday lives and experiences of ordinary people.